Numerical Simulation of Inverted Pear-shaped Landslide Based on Discrete Element Method - Bai, Jinliang (Scientific Journal of Technology, 2025)
Landslides are very common geological hazards. Due to the different forms, scales and types of landslides, their formation mechanisms are different, which in turn cause the degree of damage and treatment measures are also quite different. As a rare type of landslide, “inverted pear-shaped” landslide has special planar characteristics and formation mechanism. This paper analyzes and summarizes the different causes and formation processes of this type of landslide. MatDAM, a discrete element numerical simulation software, is used to numerically simulate the movement process of this type of landslide. According to the model comparison before and after each slide, the pushing and wrapping effect of the subsequent slide on the residual slide of the previous slide is obtained. From the perspective of numerical simulation, quantitative data support is provided for the qualitative formation mechanism study.